Faktor Lingkungan dan Perilaku yang Berhubungan dengan Kejadian Malaria di Kecamatan Panyabungan Mandailing Natal Sumatera Utara - Ahmad Faizal Rangkuti; Sulistyani Sulistyani; Nur Endah W (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2017)
Panyabungan is one of the districts in Mandailing Natal regency which is an endemic area of malaria. The number of Malaria cases until 2013 reached 36.6 ‰ in 2879 positive cases. This study aimed to determine factors related to the malaria’s occurrence. This research was observational analytic study with case control design, analyzed by logistic regression.. The result of study indicated that the area of study was in the plateu, the average of temperature and humidity is 30.8 ° C and 66.7% during the day but the everage at night is on 27.2 ° C and 71.7. Factors which significantly associated with the occurence of malaria were the use of mosquito nets (p value: 0.000; OR: 3.573 ; 95% CI: 1.732 to 7.373), the use of anti-mosquito substance (p value: 0.029; OR: 2.719; 95% CI: 1.087 to 6.798), had activity outside of the house at night (p value: 0.01; OR: 3.254; 95% CI: 1.563 to 6.777), the use of long clothes (p value: 0.013; OR: 2.474; 95% CI: 1.205 to 5.076) and the presence of stagnant water (p value: 0.033; OR: 2.33; 95% CI: 1.06 to 5.118). The dominant risk factors was not using mosquito nets at night.